Teachers' Understanding of Personality Competence and Work Discipline of High School Teachers - Maryati, Sri; Santosa, Heru; Listyasari, Winda Dewi (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study explores the suboptimal competence and work discipline of high school teachers. It aims to understand the meaning, perceptions, experiences, and real practices of teachers related to personality and discipline. A descriptive, qualitative approach was employed, utilizing purposive sampling, with experienced teachers from SMAN 42 East Jakarta. Data were collected through interviews and observations, then analyzed using the Miles and Huberman model. The findings indicate that personality competence is seen as being a role model through honesty and fairness, while discipline is reflected in a strong sense of responsibility. The primary obstacle is an administrative workload that hampers disciplinary focus, while support is provided through MGMP training and regular character-building programs. The implications underscore the importance of institutional support and policy adjustments in reducing administrative burdens, enabling teachers to focus more effectively on teaching and student character development.